A new host record for the cleptoparasite Irenangelus lucidus (Evans, 1969) (Hymenoptera: Pompilidae) - da Rocha-Filho, Léo C.; Augusto, Solange C. (Entomological Communications, 2021)
We provide a new host record for the cleptoparasitic wasp Irenangelus lucidus (Evans, 1969) (Pompilidae: Ceropalinae). A single female emerged from a brood cell of the host species Auplopus militaris (Lynch-Arribalzaga, 1873) (Pompilidae: Pepsinae) reared from a bamboo cane trap nest set at the edge of a gallery forest fragment located in Minas Gerais State, Central Brazil. This is the third host record of an Irenangelus species for the Neotropical region.